Space vehicles dynamics and control - Mohammad Abdelrahman, Mohammad Ibraheem (IIUM Press, 2011)
This book consists of two main parts main goal of the first part is to collect and develop new attitude algorithms that build up the different scenarios acted by a spacecraft starting from the orbit injection phase. The spacecraft dynamics and control oriented to the development of a simulator that simulates different attitude dynamics representations of spacecraft and the space environment in a form of disturbance torques mainly aerodynamic, gravity gradient, magnetic and solar pressure torques. It is found that the attitude scenarios can be classified mainly into two categories the first is the angular momentum management of a spacecraft and the second is the attitude maneuvers. The first category can be divided into two modes which are the detumbling mode and the momentum unloading mode. In both modes the active magnetic control algorithms have been introduced and developed. In detumbling mode the well known minus bdot control law has been modified based upon damping the angular velocity component normal to the magnetic field direction. The application results of this modified control law have shown valuable enhancement in the detumbling efficiency. In addition, the impact of the angular momentum management of the momentum/reaction wheels has been also investigated. New techniques for estimating the angular velocity without rate sensors using only vector or quaternion measurement developed via Kalman filtering have been introduced and discussed. T ii In the second category, the attitude maneuver, different techniques have been introduced starting from the classical ones such as PD controller using Euler angles, direction cosine matrix, or quaternion feed back and ended by a new approach named non-linear predictive control that developed to predict the required control action to track a certain trajectory under rate and torque constraints. Thus a new technique has be developed to solve the problem of the second category using neuro-fuzzy control to predict control torque using modelless-strategy, for attitude and rate tracking subjected to torque constraints. The simulation results give neuro-fuzzy control an edge over the new control approaches specially when considering the hard constraint of modelless spacecraft. The first part is concluded by introducing orbit dynamics and different methods for orbit control. The second part is dedicated for the spacecraft hardware. Different attitude sensors and actuators in addition to a comprehensive representation of GPS theory and utilizations, have been introduced.